Nuclear receptor CAR represses TNFalpha-induced cell death by interacting with the anti-apoptotic GADD45B. - Yukio Yamamoto (Public Library of Science (PLoS), 2010)
Background Phenobarbital (PB) is the most well-known among numerous non-genotoxic carcinogens that cause the development of hepatocellular carcinoma (HCC). PB activates nuclear xenobiotic receptor Constitutive Active/Androstane Receptor (CAR; NR1I3) and this activation is shown to determine PB promotion of HCC in mice. The molecular mechanism of CAR-mediated tumor promotion, however, remains elusive at the present time. Here we have identified Growth Arrest and DNA Damage-inducible 45beta (GADD45B) as a novel CAR target, through which CAR represses cell death. Methodology/principal findings PB activation of nuclear xenobiotic receptor CAR is found to induce the Gadd45b gene in mouse liver throughout the development of HCC as well as in liver tumors. Given the known function of GADD45B as a factor that represses Mitogen-activated protein Kinase Kinase 7 - c-Jun N-terminal Kinase (MKK7-JNK) pathway-mediated apoptosis, we have now demonstrated that CAR interacts with GADD45B to repress Tumor Necrosis Factor alpha ( TNFalpha)-induced JNK1 phosphorylation as well as cell death. Primary hepatocytes, prepared from Car(+/+), Car(-/-), Gadd45b(+/+) and Gadd45b(-/-) mice, were treated with TNFalpha and Actinomycin D to induce phosphorylation of JNK1 and cell death. Co-treatment with the CAR activating ligand TCPOBOP (1,4 bis[2-(3,5-dichloropyridyloxy)]benzene) has resulted in repression of both phosphorylation and cell death in the primary hepatocytes from Car(+/+) but not Car(-/-) mice. Repression by TCPOBOP was not observed in those prepared from Gadd45b(-/-) mice. In vitro protein-protein interaction and phosphorylation assays have revealed that CAR interacts with MKK7 and represses the MKK7-mediated phosphorylation of JNK1. Conclusions/significance CAR can form a protein complex with GADD45B, through which CAR represses MKK7-mediated phosphorylation of JNK1. In addition to activating the Gadd45b gene, CAR may repress death of mouse primary hepatocytes by forming a GADD45B complex and repressing MKK7-mediated phosphorylation of JNK1. The present finding that CAR can repress cell death via its interaction with GADD45B provides an insight for further investigations into the CAR-regulated molecular mechanism by which PB promotes development of HCC.